2024
DOI: 10.3390/pharmaceutics16010087
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization, Leishmanicidal Activity and In Vitro Cytotoxicity of the Essential Oil Extracted from Pectis brevipedunculata (Gardner) Sch.Bip. and Its Incorporation into Microemulsion Systems

Auxiliadora Cristina Correa Barata Lopes,
Jessyane Rodrigues do Nascimento,
Marcos Bispo Pinheiro Camara
et al.

Abstract: Pectis brevipedunculata (Gardner) Sch.Bip., known in Brazil as alecrim do campo, is a small Asteraceae family plant with a calming effect and consumed as tea. This species contains components, such as neral and geranial, that display various biological activities, such as leishmanicidal. The aim was to chemically characterize the essential oil (EO) obtained from P. brevipedunculata (EO-PB) by hydrodistillation and a microemulsion formulated with EO (ME-PB), Tween 80 and Transcutol P, assess the leishmanicidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…It is a small plant, rich in secondary metabolites, and native to dry and rocky environments [4,5]. The essential oil of P. brevipedunculata is mainly composed of citral, α-pinene, and limonene [4,6], which have antimicrobial, antioxidant, anti-inflammatory, and antidepressant potential [7][8][9][10]. It was also recently demonstrated that the essential oil of this species has an acaricidal effect and is selective for ladybugs and lacewings [5], raising interest in this species as a potential source for the development of novel biorational pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…It is a small plant, rich in secondary metabolites, and native to dry and rocky environments [4,5]. The essential oil of P. brevipedunculata is mainly composed of citral, α-pinene, and limonene [4,6], which have antimicrobial, antioxidant, anti-inflammatory, and antidepressant potential [7][8][9][10]. It was also recently demonstrated that the essential oil of this species has an acaricidal effect and is selective for ladybugs and lacewings [5], raising interest in this species as a potential source for the development of novel biorational pesticides.…”
Section: Introductionmentioning
confidence: 99%